Estimating the effect of entrepreneur education on graduates' intention to be entrepreneurs. Issue 8 (9th November 2015) - Mohamad, Noorkartina; Lim, Hock-Eam; Yusof, Norhafezah; Soon, Jan-Jan
Abstract : Purpose: – Previous studies on the effect of entrepreneur education are not comprehensive. Thus, estimating the effect of entrepreneur education is imperative. According to the Malaysian Ministry of Education (MoE), only 1.7 percent (as of 2013) of university graduates are self-employed, that is managing one's own business or known as graduate entrepreneurs. Consequently, a huge gap exists between what is targeted by the government (5.5 percent by 2015) and the reality (a small number of graduate entrepreneurs). The purpose of this paper is to analyze the factors influencing a graduate's choice to be entrepreneur, particularly the effects of different entrepreneur education, either formal or informal. Design/methodology/approach: – A total of 2, 300 graduates from Universiti Utara Malaysia participated in this study. Findings: – The findings showed that the majority of the respondents are consistent in terms of their intent to become entrepreneurs. Research limitations/implications: – Due to time and resource constraints, the data are limited to only one university in Malaysia. It is suggested that future studies include more universities, especially entrepreneurial universities. Although it is believe that public universities' undergraduates population are highly homogeneous, it is good that the findings of the present study to be further validated by future studies using larger sample that consists of varies of public universities. Practical implications: – This paper supports government policies in terms of cultivating educated entrepreneur such as promoting the entrepreneurship education among higher institutions of education (MoE, 2007). However, there are negative relationships among higher academic achievement of graduates toward their intention to be entrepreneurs. It is indicated that high academic achievements are negatively related to becoming entrepreneurs. Thus, it is suggested that entrepreneurship education in terms of both formal and informal education be implemented into the curriculum in order to cultivate entrepreneurial intentions. Originality/value: – There is still much more to be learned to fully understand the processes that leading to the decision to become an entrepreneur. Nevertheless, the results presented in this paper provide some understanding of the factors influencing the decision to become an entrepreneur among university students and graduates using a convenience sample. Thus, the results are exploratory and subjected to validation by future studies using more representative samples. Nevertheless, the study makes a contribution to the effort to predict and develop entrepreneurs in the country.